Análise da aplicação da teoria dinâmica do ônus da prova na caracterização de fraude à execução fiscal - Pereira, Amanda Alves (Universidade Federal do Tocantins, 2020)
The present research has as an object the fraudulent alienation in the tax enforcement and its burden of proof, having as a goal to check the possibility of application of a procedure of boosting the burden of proof at the Tax Enforcement Process, which the Court of the Public Treasury acts as a part. Although it presents the express disposition at the art. 373 of the Law of Civil Process from 2015, which has a subsidiary application to the tax enforcement, in reason of art. 1º from Law nº 6.830/80 and its use at the Tax Enforcement Process has been hampered due to inherent prerogatives to the Public Treasury, like the Supremacy of Public Interest and the legitimacy and veracity presumption of public administration acts. As a methodology was used the exploratory research through the bibliographic survey and jurisprudential analysis, through the precedent understandings which aimed to elide the existing controversies about this thematic.